Model Kompetensi Kepribadian Guru PAI Era VUCA - Muhammad Teguh Saputra (Balai Diklat Keagamaan Medan, 2023)
This study aims to describe and analyze how the personality competence model of Islamic Religious Education teachers is appropriate in the VUCA era. This study uses the literature study method by analyzing various scientific articles, books, and credible websites that are relevant to the topic that the researcher raises. Researchers conducted an analysis to filter what kind of personality is appropriate in the VUCA era according to Prof. Akhyak. Personality after being filtered, then categorized based on Bennett's scheme; volatility versus agility, uncertanity versus information, complexity versus restructuring, and ambiguity versus experimentation. The results of the study show that the appropriate personality models in the VUCA era are: (1) Volatility can managed with benefit-oriented personality, open minded, and community oriented (2) Uncertainty can managed with Islamic scholar personality, cross-difference information-digging personality, and thinker personality (3) Complexity can managed with community cooperation personality, interactive personality to the community, and interactive personality to colleagues (4) Ambiguity can managed with researcher personality, it means that PAI teachers conduct regular investigations in order to create higher quality learning.